UPAYA PENINGKATAN MINAT BELAJAR SISWA MENGGUNAKAN TWO STAY TWO STRAY (TSTS) PADA SISWA KELAS IV SEKOLAH DASAR - Apriyani, Kristiyana (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
The low learning achievement of fourth grade students is a direct result of the lack of enthusiasm for learning, so this study is important to do. Lack of interest and minimal participation in conventional class activities are clear evidence. Therefore, the application of new learning methods that are tailored to the unique characteristics of each student is very much needed to generate interest and encourage more active involvement. This study aims to evaluate the effectiveness of the Two Stay Two Stray (TSTS) learning paradigm in improving learning motivation and learning outcomes of fourth grade students. A simple quantitative method with an experimental design based on the TSTS learning model was used. Elementary school students who were randomly selected from the even semester of the 2024/2025 academic year became participants6Data were collected through assessment tests to compare achievement before and after the implementation of the TSTS model, observation sheets to monitor student involvement, and closed questionnaires to measure learning interest.Data analysis used a descriptive quantitative approach. The results showed that students responded positively to the TSTS learning model, as reflected in 77.14% of the "Good" assessments on the questionnaire. Through group work and knowledge sharing, students gain self-confidence, better questioning skills, and are able to express material in their own words. In addition, active involvement in class discussions and Q&A sessions showed high student interest and enthusiasm. The average class score also increased significantly, from 62 to 79 after the intervention. The findings indicate that the TSTS learning paradigm is able to increase students' enthusiasm for learning and achievement in class. This model encourages participation, cooperation, and deeper understanding through interactions between students and teachers. In conclusion, the Four Stay Two Stray (TSTS) learning method has a positive impact on the learning motivation and academic achievement of fourth grade students, as evidenced by an increase in questionnaire scores of 77.14% and an increase in the average score to 79 percent.